Eye involment in patients undergoin hemodialysis - Herrera Añazco, Percy (2013)
Introduction: Dialysis patients have chronic complications that impair their quality of life, such as eye involvement caused by chronic kidney disease (CKD) comorbidities, or because of specific CKD effects. This paper aims to describe funduscopy, visual acuity and intraocular pressure findings in a population undergoing chronic conventional dialysis. Material and Methods: This is a descriptive and observational crosssectional study performed in patients undergoing chronic hemodialysis in the Nephrology Service of 2 de Mayo National Hospital in Lima – Peru. Results: Thirty-one patients were studied, their average age was 62.67 ± 12.46 years, 45.16% were male, 87.1% had hypertension, and 45.16% had diabetes mellitus 45.16%. The most common ocular symptoms were blurred vision (67.74%), tearing (38.71%), pruritus (25.81%), burning sensation in the eyes (16.13%) and asthenopia (6.41%). The average intraocular pressure was 14.5 ± 5.28 mm Hg in the right eye and 14.23 ± 4.78 mm Hg in the left eye. When visual acuity was examined, we found that 6.07% of patients were blind, and poor vision was found in 39.39% of patients. Most frequent external findings were corneal and conjunctival infiltrates (41.94%), tear film alterations (35.48%), and hyperpigmentation (35.48%). Most frequent refraction defects found were hyperopia and astigmatism (80.77%). Most common well-defined ophthalmological conditions were non-proliferative diabetic retinopathy (37.93%) and age-related macular degeneration (24.14%). A bivariate analysis performed relating symptoms and final ophthalmologic diagnoses, we found that patients with blurred vision developed hypertensive retinopathy less frequently (p = 0.002) and the absence of tearing was also associated with fewer cases of hypertensive retinopathy (p = 0.03). Conclusions: Abnormal ophthalmological findings are frequently found in persons undergoing hemodialysis, and only few patients have normal visual acuity preserved. Eye examination should be routinely performed in this population.